Acute heart failure - Abadie, Eric 1964-; Abraham, William T.; Adams, Kirkwood F. Jr.; Adrie, Christophe; Albert, Nancy M.; Mebazaa, Alexandre; Gheorghiade, Mihai; Zannad, Faiez M. 1951-; Parrillo, Joseph E. (London : Springer, 2008)
For many years, there has been a great deal of work done on chronic congestive heart failure while acute heart failure has been considered a difficult to handle and hopeless syndrome. However, in recent years acute heart failure has become a growing area of study. There has been considerable amounts of new data reported and many new concepts have been proposed in the last 3-4 years looking at the epidemiology, diagnostic and treatment of acute heart failure.
La función de los autores fue determinada por el catalogador
Keywords: INSUFICIENCIA CARDIACA; INSUFICIENCIA CARDÍACA -- DIAGNÓSTICO; INSUFICIENCIA CARDIACA -- TRATAMIENTO; CORAZÓN -- ENFERMEDADES -- FISIOPATOLOGÍA; MEDICINA DE URGENCIAS